Evaluation on Performances of Carrier Based PWM for Z-Source Five Leg Inverter - Mohd. Shafie, Bakar; Kamarul Hawari, Ghazali; Hamdan, Daniyal; N. A., Rahim (2014)
On the basis of conventional five-phase Z-source inverter (ZSI), this paper presents an analysis for the performance parameter and the design parameter.